Silicosis: from pathogenesis to therapeutics - Yang, Bijun; Liu, Xiaoman; Peng, Cheng; Meng, Xiangjing; Jia, Qiang (Frontiers in Pharmacology, 2025)
Silicosis is an important occupational lung disease caused by exposure to respirable crystalline silica dust particles, with the clinical manifestations from asymptomatic forms to respiratory failure. The main pathological process involves parenchymal lung injury, inflammation and lung tissue fibrosis, but the exact pathogenesis remains elusive. Until now, there have been no effective treatments for silicosis due to the complexity of pathogenesis and irreversibility of pulmonary fibrosis. In this review we attempt to summarize the advances in pathogenesis and treatment of silicosis and to explore the current understanding of the molecular mechanisms involving in the initiation and development of silicosis and potential therapeutic targets.